Assessment of the methodological quality of studies on core outcome sets for respiratory diseases: A systematic review and meta-research study - Mengjuan Liu; Jiajia Wang; Lu Wang; Xinyi Zhang; Ruiyu Hao; Duolao Wang; Tao Chen; Jiansheng Li (PLoS ONE, 2025)
Background With increasing attention to core outcome sets (COS), the number of studies on COS for respiratory diseases (COS-RD) is on the rise. However, the methodological quality is still unclear. Therefore, we conducted a study to assess the methodological quality of studies on COS-RD. Methods PubMed, Embase, Cochrane Library, and Web of Science were searched for study protocols or original studies on COS-RD about adults, from their inception to February 23, 2024. The COMET database and Chinese databases (including China National Knowledge Infrastructure, Wanfang Data, Chongqing VIP database, and China Biology Medicine) were also searched as a supplement. Two researchers independently screened the literature, extracted the data, and assessed the methodological quality of included studies using the Core Outcome Set-STAndardised Protocol (COS-STAP) statement, the Core Outcome Set-STAndards for Development (COS-STAD) recommendations, and the Core Outcome Set-STAndards for Reporting (COS-STAR) statement. Results A total of 27 articles (five study protocols and 22 original studies, 26 studies) were included in this study. For the assessment of study protocols using the COS-STAP statement, the item with the lowest complete reporting rate was "missing data" (Item 9, 40.0%), while "description how outcomes may be dropped/combined, with reasons" (Item 5b, 60.0%) and "dissemination" (Item 11, 60.0%) had relatively low complete reporting rates. For the assessment of original studies using the COS-STAD recommendations, the item with the highest non-reporting rate was "care was taken to avoid ambiguity of language used in the list of outcomes" (Item 11, 45.5%), while "the population(s) covered by COS" (Item 3, 31.8%) and "the intervention(s) covered by COS" (Item 4, 31.8%) had relatively high non-reporting rate. When using the COS-STAR statement to assess the original studies, the item with the lowest complete reporting rate was "protocol deviations" (Item 11, 13.6%), while “describe how outcomes were dropped/combined, with reasons (if applicable)” (Item 6b, 36.4%), "participants" (Item 5, 40.9%), "ethics and consent" (Item 10, 54.5%), "protocol/registry entry" (Item 14, 63.6%), and “outcome scoring” (Item 8, 63.6%) had relatively low complete reporting rates. Conclusion The methodological quality of studies on COS-RD needs to be further improved. The appropriate use of aforementioned international reporting standards can advance the methodological quality and reporting transparency of studies on COS-RD.